Onychogomphus marijanmatoki, a new species from Sarawak, Borneo (Odonata: Anisoptera: Gomphidae) - Dow, Rory A. (Zootaxa, 2014)
Onychogomphus marijanmatoki is described from a male from Gunung Mulu National Park, Miri Division, Sarawak, Malaysian Borneo. One of only two onychogomphine species known from Borneo, it differs from all others of the group in characters of the genital ligula and terminal appendages.